METODE RESITASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Arif Hanafi Ginting (CV. Arsy Persada Quality, 2025)
In the teaching and learning process, teachers play an important role in improving the quality of education. To produce effective and efficient education, appropriate teaching methods are needed. The application of a method in teaching must be reviewed in terms of its effectiveness, efficiency and suitability to the characteristics of the subject matter and the conditions of the students which include abilities, learning speed, interests, time available and the socio-economic conditions of the students. Apart from that, learning with teaching methods that are appropriate to the material being taught is believed to increase students' learning motivation. The recitation method is a method where the teacher gives certain tasks so that students carry out learning activities. In Islamic Religious Education (PAI) learning, the maximum learning process of students can be achieved through the recitation method, which can be implemented both inside and outside the classroom and as long as it is in the school environment. The reason for using the recitation method in PAI lessons is because it is felt that there is too much learning material, while there is only a little time available. This means that the amount of material available at a time is less balanced.